Analysis of the Legal Substance of Indonesia's Bilateral Investment Treaty (BIT): Balance of Rights and Obligations Based on National Interest - Mira Nila Kusuma Dewi; Nurul Miqat; Sahlan; Sunardi Purwanda (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze Indonesia's Bilateral Investment Treaty (BIT) Law: Protection of National Interests and Balance of Rights and Obligations of Investors. This research is a type of normative research that will examine and analyze the Bilateral Investment Treaty which provides a balance between rights and obligations based on Indonesia's national interests. The data collection technique through primary legal materials, secondary and tertiary legal materials that have been collected is invertarily, processed and studied in depth so that an overview of the legal issues being studied is obtained. Data analysis is legal material that has been processed and then analyzed using qualitative methods with content analysis techniques. The results of this study conclude that Indonesia's BIT which is in force until now generally still uses the old BIT model which often causes problems with other parties in the agreement, one of which is a lawsuit through ICSID filed by investors from countries that are partners in the Agreement. Sometimes the value of claims sued by investors is sometimes too large to burden the state's finances. This is what encourages the Indonesian side to review the content of the BIT that has been made. Many BITs have been stopped and some have been amended to avoid an imbalance of rights and obligations between investors and the state. Indonesia's BIT that will be created or is currently in force can be amended by including clauses that contain human rights values, environmental protection, sustainability and economic benefits